CpaA Is a Glycan-Specific Adamalysin-like Protease Secreted by Acinetobacter baumannii That Inactivates Coagulation Factor XII - Ursula Waack (American Society for Microbiology, 2018)
ABSTRACT Antibiotic-resistant Acinetobacter baumannii is increasingly recognized as a cause of difficult-to-treat nosocomial infections, including pneumonia, wound infections, and bacteremia. Previous studies have demonstrated that the metalloprotease CpaA contributes to virulence and prolongs clotting time when added to human plasma as measured by the activated partial thromboplastin time (aPTT) assay. Here, we show that CpaA interferes with the intrinsic coagulation pathway, also called the contact activation system, in human as well as murine plasma, but has no discernible effect on the extrinsic pathway. By utilizing a modified aPTT assay, we demonstrate that coagulation factor XII (fXII) is a target of CpaA. In addition, we map the cleavage by CpaA to two positions, 279-280 and 308-309, within the highly glycosylated proline-rich region of human fXII, and show that cleavage at the 308-309 site is responsible for inactivation of fXII. At both sites, cleavage occurs between proline and an O-linked glycosylated threonine, and deglycosylation of fXII prevents cleavage by CpaA. Consistent with this, mutant fXII (fXII-Thr309Lys) from patients with hereditary angioedema type III (HAEIII) is protected from CpaA inactivation. This raises the possibility that individuals with HAEIII who harbor this mutation may be partially protected from A. baumannii infection if CpaA contributes to human disease. By inactivating fXII, CpaA may attenuate important antimicrobial defense mechanisms such as intravascular thrombus formation, thus allowing A. baumannii to disseminate. IMPORTANCE Ventilator-associated pneumonia and catheter-related bacteremia are the most common and severe infections caused by Acinetobacter baumannii. Besides the capsule, lipopolysaccharides, and the outer membrane porin OmpA, little is known about the contribution of secreted proteins to A. baumannii survival in vivo. Here we focus on CpaA, a potentially recently acquired virulence factor that inhibits blood coagulation in vitro. We identify coagulation factor XII as a target of CpaA, map the cleavage sites, and show that glycosylation is a prerequisite for CpaA-mediated inactivation of factor XII. We propose adding CpaA to a small, but growing list of bacterial proteases that are specific for highly glycosylated components of the host defense system.